Obstetric Profile of Primi Teenage and Non-teenage mothers: A comparative study from Maharashtra, India - Mohite, RV; Ganganhalli, P; Mohite, VR; Tondare, MB; Kumbhar, SM (Bangladesh Journal of Medical Science, 2013)
Introduction: Early marriages and teenage pregnancies are important contributing factors for high maternal as well as neo-natal morbidity and mortality. Objectives: To assess the magnitude of obstetric profile of teenage and non-teenage primi mothers and to determine the association among them. Methodology: A cross-sectional study was conducted at OB/Gynac clinic Krishna hospital Karad over a period of first quarter of year 2012. 93 eligible teenage primi mothers and equal number of non-teenage primi mothers admitted to Krishna hospital for delivery were enrolled, interviewed and observed for socio-demographic, obstetric outcome and its complications by investigator according to pre- designed structured proforma. Frequency percentage distribution and association was determined by applying tests of significance. Observations: Magnitude of teenage primi pregnancy was 6% during study period and most of them 92.50%, 76.30% and 46.20% were Hindus, housewives and belonged to lower class by religion, occupation and economically with mean age at marriage and delivery was 17.8 yrs and 18.8 yrs respectively. Max. 81.7% teenage primi mothers were anaemic and the percentage of obstetric complications like PIH, Oligohydramnios, PROM, Foetal distress among teenage primi mothers was 24%,8.6%, 1%, and 6.4% which was higher than nonteenage mothers. IUGR, cord prolapse, breech presentation and abruption placenta also reported among teenage primi mothers, however absent among non-teenage mothers. Max 55.9% teenage mothers were delivered before expected date of delivery and proportion of low birth weight baby was also high (39.8%) in teenage mothers than non-teenage mothers. Chance of delivery of male baby also increases as age at marriage increases. Conclusion: Adolescent pregnancy is an issue that calls for more education & support to encourage girls to delay motherhood until they are ready. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17432 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 63-66